2014
DOI: 10.4048/jbc.2014.17.3.236
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Breast Cancer in Iranian Women: A Hospital-Based Case-Control Study in Tabriz, Iran

Abstract: PurposeBreast cancer is the most common cancer in women worldwide and the leading cause of cancer death among women. In Asian countries such as Iran, the incidence of breast cancer is increasing. The present study aimed to assess the risk factors for breast cancer of women in Tabriz, Iran.MethodsA hospital-based case-control study was undertaken to identify breast cancer risk factors. The study consisted of 140 cases confirmed via histopathological analysis and 280 group-matched controls without any malignancy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
36
2
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 22 publications
10
36
2
4
Order By: Relevance
“…Most of them had no treatment record of HRT, BC record, and BC record in first rank relatives before and after menopause. The above findings are fully consistent with the results of study by Hosseinzadeh et al (20).…”
Section: Discussionsupporting
confidence: 93%
“…Most of them had no treatment record of HRT, BC record, and BC record in first rank relatives before and after menopause. The above findings are fully consistent with the results of study by Hosseinzadeh et al (20).…”
Section: Discussionsupporting
confidence: 93%
“…A study conducted in Turkey by Ceber et al (9) found no difference between the study and control groups in terms of the degree of stressor experienced in the last 5 years. On the other hand, similar to the results of the present study, it was reported that the self-reported stress in the last 5 years (15,22,23), having a stressful vital event in the last 2 years (24), and having stressful life events before the diagnosis (25) were associated with breast cancer.…”
Section: öZkan Et Al Risk Factors In Breast Cancersupporting
confidence: 90%
“…The present study also found no differ-209 ence between the controls and the study group in terms of age at first labor, and high level of labor, and breastfeeding experience in patients with breast cancer; this might be because the control group comprised of young and single women. Various studies that researched the relationship between breast cancer and abortus (15), and the use of oral contraceptives (10,14,15) reported that these factors could increase breast cancer risk. The multivariable analysis of the present study did not determine factors related to reproduction and obstetric history as independent risk factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of Hosseinzadeh et al (2014) in a case -control study demonstrated no association between high BMI and developing breast cancer (28). Low sample size, time of calculating of BMI, difference in diet and life style in area of research might be the causes of differences in results.…”
Section: Discussionmentioning
confidence: 95%